The Effective Role of Natural Product Berberine in Modulating Oxidative Stress and Inflammation Related Atherosclerosis: Novel Insights Into the Gut-Heart Axis Evidenced by Genetic Sequencing Analysis - Cao, Richard Y.; Zhang, Ying; Feng, Zhen; Liu, Siyu; Liu, Yifan; Zheng, Hongchao; Yang, Jian (Frontiers in Pharmacology, 2021)
The exacerbation of oxidative and inflammatory reactions has been involved in atherosclerotic cardiovascular diseases leading to morbidity and mortality worldwide. Discovering the underlying mechanisms and finding optimized curative approaches to control the global prevalence of cardiovascular diseases is needed. Growing evidence has demonstrated that gut microbiota is associated with the development of atherosclerosis, while berberine, a natural product exhibits antiatherogenic effects in clinical and pre-clinical studies, which implies a potential link between berberine and gut microbiota. In light of these novel discoveries, evidence of the role of berberine in modulating atherosclerosis with a specific focus on its interaction with gut microbiota is collected. This review synthesizes and summarizes antioxidant and anti-inflammatory effects of berberine on combating atherosclerosis experimentally and clinically, explores the interaction between berberine and intestinal microbiota comprehensively, and provides novel insights of berberine in managing atherosclerotic cardiovascular diseases via targeting the gut-heart axis mechanistically. The phenomenon of how berberine overcomes its weakness of poor bioavailability to conduct its antiatherogenic properties is also discussed and interpreted in this article. An in-depth understanding of this emerging area may contribute to identifying therapeutic potentials of medicinal plant and natural product derived pharmaceuticals for the prevention and treatment of atherosclerotic cardiovascular diseases in the future.